Physico – mechanical properties of multi – recycled concrete from precast concrete industry. (10th January 2017) - Salesa, Ángel; Pérez-Benedicto, José A.; Colorado-Aranguren, David; López-Julián, Pedro L.; Esteban, Luis M.; Sanz-Baldúz, Luis J.; Sáez-Hostaled, José L.; Ramis, Juan; Olivares, Daniel
Abstract: The construction industry must adapt to new environmental requirements and becomes more sustainable. Recycling concrete waste to produce new concrete is one of the main ways of reducing the construction industry environmental impact. In the precast industry some of the concrete elements produced are rejected due to quality test failures. These products can be crushed to produce aggregates and reintroduce them in the manufacturing process. There are many investigations have been focused in the use of recycled concrete aggregates in concrete mixes, but very few have researched the possibility to recycle the concrete that have already been recycled. The aim of this study is to analyse the effect of incorporating recycled and multi-recycled coarse aggregates from rejected precast concrete to make a new concrete. The key properties of the recycled and multi-recycled new concrete were compared with a control concrete made from natural coarse aggregates. The fresh and hardened properties were assessed by the metrics: workability, density, absorption, compressive strength and modulus of elasticity. The results showed that the concrete from recycled and multi-recycled coarse aggregates have the equivalent behaviour to the control concrete. The compressive strength is slightly higher in the first and second recycled concretes than the control concrete, also there has been a decrease in the density of recycled concretes with respect to control; these differences increased with each cycle of recycling. Due to the usage of high quality precast parent concretes a good structural behaviour was expected, with increments up to 5% in the compressive strength. The use of recycled and multi-recycled coarse aggregates from precast concrete industry can produce high quality concrete and decrease the environmental impact by waste recycling. Highlights: Making recycled concrete with multi-recycled concrete aggregates from precast industry. The recycled and multi-recycled concrete have the similar characteristics to control. Precast industry may have a good quality source of aggregates grinding its concrete waste. Precast concrete industry becomes environmentally friendlier using with the use of multi-recycled aggregates.